A disaster preparedness plan for the Manila City Library - Luz, Redentor Bien C., Jr.; Buenrostro-Cabbab, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
This study aims to find out how prepared the Manila City Library for disasters and what can be done to improve its disaster preparedness.
The researcher used descriptive and qualitative research strategy in doing the study. The researcher conducted an interview with the officer-in-charge of the Manila City library and distributed survey questionnaires to the staff of the library. Twenty-two out of the 30 staff members were able to answer the questionnaire. The researcher made an on-site observation at the library and conducted a risk assessment using the IFLA Disaster Preparedness and Planning Manual (2006) as a guide.
Overall findings show that the Manila City Library is not prepared for a disaster. The library is in a disaster-prone area. It is located at a place where flooding is a common occurrence. Based on The National Building Code of the Philippines (1972), the building is deemed unsafe due to lack of adequate number of exits and the stairway having insufficient width. The library does not have a disaster plan or a disaster team. The library only employs basic preventive measures and it has limited resources to use in an event of a disaster. There are also no clear response and recovery procedures during and after a disaster.
It is recommended that the library should have its own disaster preparedness plan and a disaster preparedness team. The researcher proposed a disaster preparedness plan at the end of study which the library may use.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Manila City Library; Emergency management -- Philippines -- Manila